Equity in Digital Health: Assessing Access and Utilization of Remote Patient Monitoring, Medical Apps, and Wearables in Underserved Communities - Omolola Adepoju PhD, MPH; Patrick Dang BS; Holly Nguyen; Jennifer Mertz RN, MSN, NEA-BC (SAGE Publishing, 2024)
This study examined access to, and use of remote patient monitoring (RPM), medical applications, and wearables in a racially diverse, lower-income population. Data were obtained via a cross-sectional survey of adults from low-income communities in Houston, Los Angeles, and New York between April and August 2023. The survey examined access to, and use of RPM, medical applications, and wearables, among respondents. Binary responses to the following questions were examined using logistic regression models: In the past 12 months, have you (i) used RPM, (ii) used a medical app, and (iii) used an electronic wearable device to monitor or track health or activity? A total of 305 surveys were returned, of which 212 were complete (69.5% completion rate). Demographically, 22% self-identified as Hispanic, 41% as non-Hispanic Black individuals, and 33% as non-Hispanic White individuals. Overall, 69% of respondents reported a pre-tax annual household income of less than $35 000 and 96﻿% indicated they own a smart phone. However, only 3 of 10 reported using RPM, 15% reported using a medical app, and 14% reported using wearables. Race was strongly associated with RPM usage, with Black respondents significantly less likely to have used RPM, compared to their white counterparts (OR: 0.31, P = .002). Education (bachelor's degree or more OR: 4.79, P = .03) and higher income ($35 001 + OR: 4.68, P = .008) were strongly associated with medical app usage. In the wearables model, the same trend was observed with education (bachelor's degree or more OR: 4.45, P = .04), and higher income ($35 001 + OR: 5.49, P = .01). Compared to earlier studies that have reported utilization rates of between 50% and 60%, our finding of much lower utilization in economically disadvantaged populations that are at greater risks for sub-optimal health outcomes gives cause for greater concern. Considering the ongoing proliferation of digital health technological modalities, this further highlights the need to explore and address equity-based barriers to these health tools.